Characteristics of pediatric patients with febrile convulsions admitted to a tertiary care hospital in Riyadh, Saudi Arabia - Alanoud A. Abuhaimed; Nawaf A. Alghamdi; Ghadah I. Alhussin; Ghadah S. Alduhaimi; Fatmah Othman; Duaa M. Baarmah; Hamad A. Alkhalaf (Journal of Family and Community Medicine)
BACKGROUND: Febrile convulsions (FCs) are the most common type of seizures in children. They usually occur between the ages of 6 months and 5 years and affect 2%–5% of children worldwide. The aim of this study was to describe the epidemiological and clinical characteristics of children who have been diagnosed with FCs and admitted to a tertiary care hospital in Riyadh. MATERIALS AND METHODS: The study included pediatric patients aged between 3 months and 5 years who presented to the emergency department of King Abdullah Specialist Children’s Hospital in Riyadh, Saudi Arabia and were admitted to hospital with FC diagnosis during 2015 to 2021. The hospital’s electronic medical records system was reviewed to obtain patients’ information on age, gender, clinical characteristics, laboratory investigations, length of hospital stay, and outcome. Data was analyzed using Stata 12; Chi-square test was used to determine association between categorical variables, while t-test or Mann–Whitney U test compared continuous data between two groups. RESULTS: A total of 247 children with FC diagnoses were included in the analysis; 0.4% of pediatric patients were admitted to the hospital with the diagnosis of FC. Most of the patients (77%) convulsions were triggered by upper respiratory tract infections and median duration of the convulsion episode was 4 min; 55% of the patients had a simple FC, and 40% had recurrence of FCs. Developmental delays were more common in children with recurrent FCs (15%) compared to children who had only one episode of convulsion (2.7%) [P < 0.001]. CONCLUSION: During the study period, 0.4% of pediatric patients were admitted to hospital with FC diagnoses. Larger multicenter studies are needed to evaluate FCs based on their clinical and operational characteristics to improve the quality of care, decrease the length of patient hospital stay, and lower the recurrence rate.